Heavy metals in water, sediment and Whiteleg shrimp (Litopenaeus vannamei) from aquaculture ponds in Likas, Sabah - Lee, Wei Peng (2019)
The issue of heavy metal toxicity has received considerable attention in aquaculture field. Most studies of heavy metal in aquaculture have only focused on fish species and molluscs but not shrimp. Thus, the key research objective of this study is to identify and study selected heavy metals in water, sediment and Litopenaeus vannamei (Whiteleg Shrimp) in the study area. In this study, the water samples were filtered and preserved with acid while for the mature shrimps (5 months old) and sediment were collected and dried. Sample of 1g (shrimp and sediment) and 1 ml (water) were digested using H2SO4 and HNO3 for 2 hours and filtered. The heavy metal concentration in water, sediment and shrimp samples was determined using ICP-OES. The water sample multivariate statistical analysis showed that primary contributing heavy metals are Cu, Fe, Mn and Zn, followed by Cd and Pb and least contributing heavy metals is Cr and Ni in water. Heavy metals in sediments shows the abundant heavy metals is Fe, Cr, Mn and Zn while the least abundant is Pb and Cd. The present research shows the ranking profile of heavy metals concentration is Fe> Cu> Zn> Cr> Mn> As> Ni> Pb> Cd. Most of the heavy metals are accumulated in the head of the shrimp whereas the least is in the shell of shrimp. In this research, all BCFp-w values are classified under low potential. It was found the BCFp-s values for Cu for shrimp head (BCFp-s=26.84), shrimp flesh (BCFp-s= 3.36) and shrimp shell (BCFp-s=18.11) are highest. This indicates that the shrimp contained more metals than sediment. The BCFp-s values for Cd, Cr, Fe, Mn, Ni and Pb were lower than 1.0, which means limited ability of these heavy metals to be accumulated by the shrimp. In this research, it is shown that bioaccumulation of heavy metals in shrimp and water are negative relationship while it shows positive relationship between heavy metals concentration in water quality and sediment. Bioaccumulation of heavy metals in shrimp and sediment shows similar trend which is negative relationship.